Analysis of Drug Logistics Management at Bunut Community Health Center, Pelalawan Regency in 2023 - Ella Irmayeni; Budi Hartono; Zul Akbar (LPPM Universitas Harapan Bangsa, 2024)
The availability of medicines is currently a demand for health services, so they must be available at all times so that health services can run optimally. Drug control at the Bunut Community Health Center cannot be carried out optimally because the demand for drugs is sometimes not met due to shortages of drugs from the Health Service and inadequate facilities and infrastructure. The research objective is to analyze drug logistics management through input and process components using a qualitative descriptive approach method with in-depth interviews with the Community Health Center. There were 3 informants, namely the pharmacist as the BLUD treasurer, the planning pharmacist and the pharmaceutical installation (logistics) pharmacist assistant who best understands the budget and flow of planning, requesting, storing, distributing, destroying and controlling is the pharmacist in charge of logistics. So, for this residency activity, I chose informants who were competent and capable so that I could understand information related to logistics at the Bunut Community Health Center in its entirety from the Bunut Community Health Center aspect. The data collection method is in-depth interviews and research. Data analysis uses problem solving cycle techniques including situation analysis, problem identification, problem priorities and determining alternative problems using Fishbone analysis and Plan of action. The priority problem in this research is that drug control at the Bunut Community Health Center has not been implemented optimally. There are still drugs received that do not meet needs. It is hoped that the community health center can communicate and coordinate periodically existing problems with all stakeholders, especially the Pelalawan district health office so that drug needs are met and the budget is appropriate and it is hoped that the Health Service will fulfill all drug requests